THE ROLE OF BRAND MARKETING IN INFLUENCING CUSTOMER DECISIONS (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In recent years, with the development of the market economy and the increasing trend of growth in many areas of the national economy, countries have become more widely used, even in some sense "fashion" from English "brand", "branding", "promote the brand" They mastered the words "to do". Branding is a complex concept covered in several articles and many textbooks. However, most people do not have a clear idea about the brand. Due to the complexity of this concept, it is often confused with a trademark. For example, the Oxford dictionary defines the concepts of "branding" and "branding" as follows. "Brand (brand) - a set of all representations, ideas, images, associations, etc. about a specific product that is relevant to consumers and tells them: "Yes, this is what I need to buy." We can say that such a brand is a reputable and well-known brand. However, a number of experts argue that brand and branding should not be confused. Brands of well-known companies have a large amount of funds.